A role for extracellular amastigotes in the immunopathology of Chagas disease - Scharfstein,Julio (1999)
In spite of the growing knowledge obtained about immune control of Trypanosoma cruzi infection, the mechanisms responsible for the variable clinico-pathological expression of Chagas disease remain unknown. In a twist from previous concepts, recent studies indicated that tissue parasitism is a pre-requisite for the development of chronic myocarditis. This fundamental concept, together with the realization that T. cruzi organisms consist of genetically heterogeneous clones, offers a new framework for studies of molecular pathogenesis. In the present article, we will discuss in general terms the possible implications of genetic variability of T. cruzi antigens and proteases to immunopathology. Peptide epitopes from a highly polymorphic subfamily of trans-sialidase (TS) antigens were recently identified as targets of killer T cell (CTL) responses, both in mice and humans. While some class I MHC restricted CTL recognize epitopes derived from amastigote-specific TS-related antigens (TSRA), others are targeted to peptide epitopes originating from trypomastigote-specific TSRA. A mechanistic hypothesis is proposed to explain how the functional activity and specificity of class I MHC restricted killer T cells may control the extent to which tissue are exposed to prematurely released amastigotes. Chronic immunopathology may be exacerbated due the progressive accumulation of amastigote-derived antigens and pro-inflammatory molecules (eg. GPI-mucins and kinin-releasing proteases) in dead macrophage bodies.